2018
DOI: 10.1088/1674-1056/27/12/126101
|View full text |Cite
|
Sign up to set email alerts
|

Review of improved spectral response of ultraviolet photodetectors by surface plasmon

Abstract: Ultraviolet (UV) photodetectors based on wide band gap semiconductor have attracted much attention for their small volume, low working voltage, long lifetime, good chemical and thermal stability. Up to now, many researches have been done on the semiconductors based UV detectors and some kinds of detectors have been made, such as metalsemiconductor-metal (MSM), Schottky, and PIN-type detectors. However, the sensitivity values of those detectors are still far from the expectation. Recent years, surface plasmon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Generally, Ag and Au nanoparticles (NPs) are ideal candidates for improving the performance of optoelectronic devices [171,172] . However, the plasmon frequencies of these metals are less than the frequency of solar-blind UV light, so they are not suitable for further application in SBPDs [173] . Zhang et al found that the plasmon frequency of Al NPs could match with that of solar-blind UV light, and they realized remarkable plasmon resonance on Al 0.54 Ga 0.46 N MSM SBPDs [153] .…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 99%
“…Generally, Ag and Au nanoparticles (NPs) are ideal candidates for improving the performance of optoelectronic devices [171,172] . However, the plasmon frequencies of these metals are less than the frequency of solar-blind UV light, so they are not suitable for further application in SBPDs [173] . Zhang et al found that the plasmon frequency of Al NPs could match with that of solar-blind UV light, and they realized remarkable plasmon resonance on Al 0.54 Ga 0.46 N MSM SBPDs [153] .…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 99%
“…When the oscillation frequency matches with the frequency of the external optical field, surface plasmon resonance (SPR) occurs. In metal NPs, the resonant excitation of the SPs is localized around the NP and consequently termed as LSPR [17][18][19][20]. LSPR has been utilized to improve the performance of semiconductor UV PDs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, selfpowered photodetectors possess the advantages of fast time response and high responsivity. Some researchers have fabricated self-powered photodetectors based on various structures, such as, Schottky junction, [1,2] p-n junction, [3,4] and photo electrochemical cell. [5] Although self-powered photodetectors have been developed for many years, their performances still cannot meet the requirement of commercially application at present.…”
Section: Introductionmentioning
confidence: 99%